Generalized PIC Detector for Distributed STBC under Quasi-Synchronization - Astal, Mohammed T.; Abu-Hudrouss, Ammar M. (Scientific Research Publishing, 2012)
In this paper, we propose a Generalized Parallel Interference Cancelation (G-PIC) approach for the detection of D-STBC under Quasi-Synchronization in the case of any number of relay nodes with just statistical information about time misalignment. While as, most researches assume perfect synchronization between the relay nodes for the detection of D-STBC which is hard to achieve. This approach proved to be very effective to mitigate the degradation in the system performance due to the imperfect synchronization. The numerical simulations, for the proposed approach, showed that in just three iterations we can achieve performance close to the D-STBC with perfect synchronization.
Keywords: Distributed Space Time Block Coding; Synchronization; Distributed Transmit Diversity; Cooperative Diversity